Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 7 - Section 7.3 - Simplifying Radical Expressions - Exercise Set - Page 433: 55


$3x^{3}y^{4}\sqrt (xy)$

Work Step by Step

$\sqrt (9x^{7}y^{9})=\sqrt (9\times x^{6} \times y^{8}\times xy)=\sqrt 9\times \sqrt (x^{6})\times \sqrt (y^{8})\times \sqrt (xy)=3x^{3}y^{4}\sqrt (xy)$ We know that $\sqrt 9=3$, because $3^{2}=9$. We also know that $\sqrt (x^{6})=x^{3}$, because $(x^{3})^{2}=x^{3\times2}=x^{6}$ and that $\sqrt (y^{8})=y^{4}$, because $(y^{4})^{2}=y^{4\times2}=y^{8}$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.